The paths not (yet) taken: Ulrich Beck, the 'cosmopolitized world' and security studies. (October 2016) - Selchow, Sabine
While it is Ulrich Beck's concept of 'risk society' that has mostly attracted attention in the field of security studies, in this article I argue that if we want to take Beck seriously, we need to go beyond his 'risk society' thesis and acknowledge that his main thesis was that we live in a social reality that is qualitatively new and, consequently, calls for a radical shift in how we look at and talk about it. To bring Beck into security studies, then, means to study 'security' from within Beck's 'new world'. For that, I argue, a sharper conception of what characterizes that world is needed. At the heart of my article I provide such a conception – the 'cosmopolitized world' – which I identify as being shaped by non-linearity and the interplay of two moments: the 'cosmopolitized reality' and the 'tradition of the national perspective'. Building on this concept and experimenting with it, I turn to reading the 'US national security' discourse as this is constructed in the text of the 2015 National Security Strategy from within this 'cosmopolitized world'. Reflecting on this experiment, I conclude by highlighting the potential that bringing Beck in this way into security studies holds, as well as pointing to the need for future work on the vocabulary of the 'cosmopolitized world'.